Nucleolar organizer region (AgNOR) staining on fibrocystic change of the breast. - Ahmad Ghozali, Ahmad Ghozali (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1997)
In the past the fibrocystic change of breast was considered as a precancerous lesion, consequently the management of a fibrocystic patient was often overdone. Later, after thorough researches, it has been histologically (Page classification) proven that only small part of the changes have high risk to become invasive carcinoma. The leading factor which increases the risk is the grade of proliferation of the gland epithelia. AgNOR stain is a staining method to evaluate cell proliferation activity which has been proven as one of tools for the assessment of the prognosis of several malignant tumors including breast cancer. in this study the amount of AgNOR in fibrocystic change was studied based on Page classification. Nineteen fibrocystic cases classified by Page were stained with colloidal silver. NORs were counted manually. The mean of AgNOR of each classification, normal gland, and carcinoma was compared. There were significant differences of AgNOR count found between each classification, normal gland and carcinoma. The AgNOR count of non proliferative lesion were 2.074 ÃÂ± 0.320, proliferative disease without atypia 2.416 ÃÂ± 0.35, atypical hyperplasia 2.876 ÃÂ± 0.249, normal gland 1.637 ÃÂ± 0.330, and in carcinoma 4.407 ÃÂ± 0.340. The result demonstrated that the AgNOR staining is a reliable marker for proliferation activity, and can differentiate atypical hyperplasia from carcinoma. The determination of AgNOR count can be done routinely to follow up and monitor the high risk lesions.Key words: fibrocystic change - Page classification - nucleolar organizer.